1979
DOI: 10.1002/ana.410060105
|View full text |Cite
|
Sign up to set email alerts
|

Metals in spinal cord tissue of patients dying of motor neuron disease

Abstract: To evaluate the role of toxic metals in causing motor neuron disease (MND), we used a photon-excited, energy-dispersive x-ray analytical system to measure the metal content of spinal ventral horn tissue. Specimens were taken from the cervical and lumbar enlargements of 7 patients who died of MND and the results compared with those found in 12 control patients. Anterior horn lead levels were elevated in MND patients compared to controls (mean, 40.7 micrograms/gm versus 14.6 micrograms/gm; p less than 0.05) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 14 publications
2
32
2
1
Order By: Relevance
“…However, these results were in contradiction with the ones obtained by Khare et al [55]. Kurlander and Patten [54] found that in the anterior horn tissue the iron content was higher (P < 0.05) in seven ALS patients than in 11 controls with neurological and non-neurological diseases. Nagata et al [61] showed that the Mn concentrations in blood cells from ALS patients were significantly lower than from controls (non-ALS subjects).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…However, these results were in contradiction with the ones obtained by Khare et al [55]. Kurlander and Patten [54] found that in the anterior horn tissue the iron content was higher (P < 0.05) in seven ALS patients than in 11 controls with neurological and non-neurological diseases. Nagata et al [61] showed that the Mn concentrations in blood cells from ALS patients were significantly lower than from controls (non-ALS subjects).…”
Section: Discussioncontrasting
confidence: 76%
“…Dysmetabolism of Zn was also reported for ALS patients in spinal cord and blood. Zn was found to be either unchanged, decreased, or increased [52,[54][55][56]. Kapaki et al [30] has found decreased levels of Cu in CSF, whilst Zn, Mn and Mg levels were unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggests that people with sporadic ALS also have elevated levels of copper (and other metals) in the motor area of their spinal cords (20). However, a small human trial of a copper chelator showed no benefit (21).…”
Section: Mechanismsmentioning
confidence: 99%
“…Lead can cause peripheral neuropathy and encephalopathy in humans, with a dose-effect relationship existing between blood levels and clinical findings [19]. Lead concentrations are elevated in the anterior horn cells of ALS patients previously exposed to high levels of lead [20] and may cause upper motor neuron degeneration in predisposed individuals.…”
Section: Assessment Of Environmental Risk Factors and Gene-environmenmentioning
confidence: 99%